الهويّة الثّقافيّة الجزائريّة بين التّنوع ورهانات الوحدة الوطنيّة: Algerian Cultural Identity between Diversity and Aspirations of National Unity - شايب الدراع وليد; بخوش نجيب (Maalim, 2022)
In this study, we tried to address the issue of Algerian cultural identity and identify its various dimensions. The Algerian identity as it is known is a rich and multiple identity within which multiple identities are competing. This richness includes many aspects such as linguistic, ethnic and cultural aspects all of which make the Algerian cultural identity as a universal identity of different attributes. In this regard, some may consider that it poses problems in integration and challenges the aspirations of national unity and this belief is certainly based on an incorrect idea in which identity is seen as reduced in one dimension. However, through this paper, we seek to emphasize that the issue of diversity and cultural, linguistic and ethnic multiplicity is a powerful element of the Algerian cultural identity, as a result, we have found that the issues of cultural identity must not be left as a tool in the hands of politicians, in addition to the importance of establishing values of citizenship and coexistence through several means mainly the educational curricula